Karakter Kuantitatif Delapan Galur Baru Tomat (Lycopersicum esculentum) Generasi F6 di Dataran Rendah - Eka Erlinda Syuriani; Jaenudin Kartahadimaja; Miranda Ferwita Sari; Bambang Purwanto (J-Plantasimbiosa, 2021)
Tomato production can’t fulfill the consumption needs of tomatoes. One way to fulfill this need is to expand the land by planting tomatoes in the lowlands. However, the limited number of cultivars suitable for planting in the lowlands is an obstacle. Assembling new superior cultivars of tomato plants that have good adaptations in the lowlands is one solution that can be done. The aim of this research was to produce a new tomato strain with superior characters. The research design was using a Completely Randomized Block Design, as a treatment consisting of eight new strains of F6 generation tomato plants, each experimental unit was repeated three times. The variables observed were maximum plant height, number of primary branches per plant, number of fruit bunches per plant, number of fruit per bunch, number of fruit per plant, age of plant beginning to flower, age of fruit starting to form until physiological maturity, fruit diameter, the weight of each fruit, fruit yield per plant, fruit yield per hectare. The data were analyzed for variance, if there was a significant difference between treatments; further tests were carried out with the BNT test at an alpha of 0.05. The results showed that each strain had various quantitative characters. The LA, LA1, and LH strains had a higher potential yield per hectare compared to the other lines. The heritability values in most of the observed quantitative variables have moderate to high values. This shows that the character is more controlled by genetic traits. Keywords: quantitative character, strain, tomato